Post Traumatic Chronic Encapsulated Intracerebral Hematoma in a Child: Case Report and Brief Review of Literature - Roka, Yam Bahadur; Karki, Mohan (Nepal Journal of Neuroscience, 2017)
Chronic encapsulated intracerebral hematoma (CE-ICH) is an uncommon pathology that presents with headache, seizure, focal neurological deficits, or as a tumor. Trauma as a cause for CE-ICH is even rare and we believe this is the first case report as “trauma causing chronic encapsulated intracerebral hematoma “search in PubMed did not reveal any results. Repeated micro-hemorrhages in the CM or AVM are supposed to cause this lesion which progress from an earlier encapsulated phase to a thick capsulated stage with edema and clinical symptoms. CT or MRI is the diagnostic modality and it mimics, tumor, AVM, CM, angiomableed, cerebral abscess, metastatic mass or neurocysticercosis. Burr hole, mini-craniotomy, craniotomy, CT guided stereotactic aspiration or endoscopic excision are some options with equally good results. The present case with history of trauma was managed successfully with craniotomy with no recurrence for past one year. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, page: 46-48